Humanistic Approach in Building Ethical Resilience and Empathy: A Case Study at SDN Madyopuro 2 - Aulia Al Tsani Izzati; Oktaviani Adhi Suciptaningsih; Ade Eka Anggraini (Eduvest - Journal of Universal Studies, 2025)
This case study examines the impact of a humanistic approach on the ethical resilience and empathy of students at SDN Madyopuro 2. The humanistic approach helps students achieve academically and grow socially and emotionally. A qualitative case study design was employed to capture practices observed in grades 4 and 6, utilizing classroom observations, in-depth interviews, and document analysis. The implementation of key strategies, including value-oriented activities, reflective dialogues, and collaborative learning, proved instrumental in fostering moral resilience and empathy among students. These methods enabled students to navigate ethical dilemmas and cultivate a more profound interpersonal understanding. Success depended on educators adopting a student-centered approach and the school principal’s support. However, the implementation of these strategies could have been improved by addressing challenges such as limited time and resistance to change. These findings highlight the necessity for systemic and cultural transformations to realize the full potential of humanistic education. This research supports the use of humanistic approaches in primary character education. It provides actionable insights for educational institutions seeking to implement strategies that promote holistic student development, thereby making a meaningful contribution to the discourse on character education.